Hazard‐consistent simulated earthquake ground motions for PBEE applications on stiff soil and rock sites - Alvarez‐Sanchez, Luis Guillermo; Iñárritu, Pablo García de Quevedo; Šipčić, Nevena; Kohrangi, Mohsen; Bazzurro, Paolo (Earthquake engineering & structural dynamics, 2023)
Ground motion record selection is a standard step in state‐of‐the‐art performance‐based earthquake engineering (PBEE) applications. It links the structural response to seismic hazard of the site of interest. In this process, suites of hazard‐consistent ground motion recordings of a wide range of intensity levels are selected (and often scaled) from a database of ground motions to be used as input to nonlinear dynamic response analysis. The ideal practice would be to select ground motions from a database of recorded accelerograms in such a way that they are consistent with the seismic hazard at as many intensity measure (IM) levels as possible and for all important causative scenarios. However, the available databases are not heavily populated, especially for the large‐magnitude short‐distance scenarios. Therefore, synthetic ground motions are the natural candidates to enlarge the database of recordings for scenarios that are important to the site hazard but lack, completely or partially, recorded accelerograms. The usage of such recordings, however, can be recommended only after they are proven to be “realistic” through a battery of seismological and statistical tests. In this study, we propose and implement a multi‐fold testing framework for such an evaluation. We first generate a ground motion database of simulated ground motions (SDB) whose values of the parameters of the causative earthquakes are, to the extent possible, the same of those that caused the ground motions in a mirror database of recorded ground motions (RDB). We then utilize the conditional spectrum (CS) approach computed for a hypothetical rock site in Perugia, Italy, to select hazard consistent records separately from the RDB and SDB databases. A comprehensive set of comparisons of distributions of several IMs, computed from the selected sets, and of distributions of engineering demand parameters (EDPs), that such record sets induce on simple SDoF structures suggests the adequacy of using the proposed simulated ground motions for structural response analyses of structures on stiff and rock sites.